Study on a Novel natural cellulosic fiber from Kigelia africana fruit: Characterization and analysis. (15th September 2020) - Siva, R.; Valarmathi, T.N.; Palanikumar, K.; Samrot, Antony V.
Highlights: Physical, chemical, thermal characteristics, surface morphology analysis of the Kigelia africana fiber were studied. Chemical and FTIR analysis affirm cellulose, hemicellulose and lignin. Surface morphology of the Kigelia africana fiber was studied by Scanning electron microscopy. Abstract: In recent days, there is an increasing use of green composites in composite manufacturing, where cellulosic natural fibers have been started using for this purpose. In line with this, a novel cellulose fiber was extracted from the Kigelia africana fruit and its physical, chemical and thermal properties, crystallography and surface morphology analysis were studied and reported in this investigative research paper. The physical analysis revealed the mean tensile strength as 50.31 ± 24.71 to 73.12 ± 32.48 MPa, diameter as 0.507 ± 0.162 to 0.629 ± 0.182 mm and density as 1.316 g/cm³ for the Kigelia africana fiber. The proximate chemical analysis estimated the cellulose percentage to be 61.5 % and the existence of different basic components like cellulose, hemicellulose and lignin are confirmed by Fourier transform infrared spectroscopy analysis. Thermogravimetric analysis establishes the thermal stability of the fiber as 212 ⁰C. The crystallinity index, 57.38 % of the fiber was determined by X-ray diffraction. Surface morphology by field emission scanning electron microscopy reveals the presence of protrusions in fiber which aid in the better adhesion with the matrix in composite manufacturing.